Measuring the Green Infrastructure Resilience in Turkey - Berfin KARABAKAN; Yelda MERT (Chinese Journal of Urban and Environmental Studies, 2021)
Cities today face significant difficulties and even risks due to the negative effects of climate change, uncontrolled urbanization, and rapid population growth. Many urban scenarios are being developed to mitigate potential risks and threats. One branch of these scenarios is built upon the concept of sustainability, for which the notion of “resilience” is of utmost importance. It is this notion of resilience that was examined in this study, based on the case of socio-ecological system features of Edremit, Van, Turkey. These features were evaluated in terms of changes that will potentially take place, and the analysis for this was performed using the Green Infrastructure Spatial Planning (GISP) method. In this approach, green infrastructure benefit criteria are mapped in the Geographic Information System (GIS) environment and various conclusions are drawn from the evaluation of these maps. The results of the study show that the green infrastructure systems of Edremit play an important role in providing a certain degree of resilience. It was, therefore, revealed as part of this study that measuring and evaluating the resilience properties of different cities is important. Also, urban policies and spatial strategies should be defined considering local characteristics and values as there is no one-size-fits-all solution in this regard.